Work Facility Improvement of a Motorcycle Wash Station in Deli Tua District, Deli Serdang Regency - Yahya, Idhar; Siregar, Khawarita; Anizar, Anizar; Gunawan, Andri (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Aqila Wash Station is a micro business that washes motorcycles, mats and carpet in Deli Tua, a sub-district in North Sumatra province. Washing motorcycle may consume a large amount of time and this decreases customers’ satisfaction. The whole process is performed manually using very simple tools and this tires the workers quickly, which results in a decrease in their work quality. The most common problem that workers face is soap depletion. The next problem is compressor machine becomes hard to initiate, which makes the washing duration longer and may even cause customers to go to another motorcycle wash station. This service activity helps the wash station by providing a compressor machine and a set of hydraulic tools to raise and lower the motorcycle. The floor, where the motorbike is washed, is leveled, and then a steam machine and soap are provided. This service activity also includes giving assistance to the workers, rotating the material given, providing internships chance to students, and teaching few concepts of science and technology. It is expected that workers effectiveness will improve the work quality of Aqila Wash Station.